2003
DOI: 10.1251/bpo55
|View full text |Cite
|
Sign up to set email alerts
|

Application of 4,5-diaminofluorescein to reliably measure nitric oxide released from endothelial cellsin vitro

Abstract: Here we describe in more depth the previously published application of the fluorescent probe 4,5-diaminofluorescein (DAF-2) in order to reliably measure low levels of nitric oxide (NO) as released from human endothelial cells in vitro. The used approach is based on the following considerations a) use low concentrations of DAF-2 (0.1 µM) in order to reduce the contribution of DAF-2 auto-fluorescence to the measured total fluorescence, and b) subtract the DAF-2 auto-fluorescence from the measured total fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 36 publications
1
63
0
1
Order By: Relevance
“…The finding that this background emission is equivalent to the activation of 2 µM of DAF-2-T within the tissue attests to its significance and potential for interfering with the detection of DAF-2 T formation. The importance of DAF-2 autofluorescence was first pointed out by Leikert et al [9] and Rathel et al [10] in the context of DAF-2 in tissue perfusates, which our results now extend to tissue NO bioimaging.…”
Section: What Is the True Sensitivity Of Daf-2 For Imaging No Sourcessupporting
confidence: 79%
See 3 more Smart Citations
“…The finding that this background emission is equivalent to the activation of 2 µM of DAF-2-T within the tissue attests to its significance and potential for interfering with the detection of DAF-2 T formation. The importance of DAF-2 autofluorescence was first pointed out by Leikert et al [9] and Rathel et al [10] in the context of DAF-2 in tissue perfusates, which our results now extend to tissue NO bioimaging.…”
Section: What Is the True Sensitivity Of Daf-2 For Imaging No Sourcessupporting
confidence: 79%
“…A number of studies have reported on the nitrosation of DAF-2 for varying concentrations of NO donors, either in buffer solutions [9,10,20,21,30] using fluorometry or in cells/tissues [26,29] using fluorescence microscopy. …”
Section: Comparative Nitrosation Of Daf-2 In Buffer Solutions and Tismentioning
confidence: 99%
See 2 more Smart Citations
“…Of these analyses however, only fluorometric and electrochemical have both the sensitivity and flexibility to measure low levels of constitutively produced NO from cultured cells in situ. Particularly, the fluorescent indicator diaminofluorescein (DAF) has been used to quantify NO generated by cultured myofibroblasts [21] [22]. While this method is highly sensitive, it has had limited success due to the susceptibility of the calibration standard to photolysis.…”
Section: Introductionmentioning
confidence: 99%